Wojna o tron hospodarski w Mołdawii w latach 1615-1616 i jej wpływ na stosunki polsko-osmańskie - Constantinov , Valentin (Saeculum Christianum. Pismo Historyczne, 2020)
The Moldavian campaign in late 1615 and first half of 1616 caused a growing tension in the relations between the Republic of Poland and Ottoman Empire. The Turkish sultan was determined to defend his interests in Moldova. At the same time, the Polish king tried to gain the throne of Moscow. The Polish magnates, Michał Wiśniowecki and Samuel Korecki, married to daughters of Elisabeta Movilă, decided to put their brother-in-law, Alexander Movilă, on the throne of Moldavia. But Hetman Stanisław Zółkiewski and king Sigismund III were against this campaign and did not provide any support. The intervention in Moldova could have had serious consequences for both the Turks and the Tatars. The war ended in the defeat of the magnates.